A Direct Aspiration, First Pass Technique (ADAPT) versus Stent Retrievers for Acute Stroke Therapy: An Observational Comparative Study - Lapergue, B.; Blanc, R.; Guedin, P.; Decroix, J.-P.; Labreuche, J.; Preda, C.; Bartolini, B.; Coskun, O.; Redjem, H.; Mazighi, M.; Bourdain, F.; Rodesch, G.; et al. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Mechanical thrombectomy with stent retrievers is now the standard therapy for selected patients with ischemic stroke. The technique of A Direct Aspiration, First Pass Technique for the Endovascular Treatment of Stroke (ADAPT) appears promising with a high rate of recanalization. We compared ADAPT versus stent retrievers (the Solitaire device) for efficacy and safety as a front-line endovascular procedure.MATERIALS AND METHODS: We analyzed 243 consecutive patients with large intracranial artery occlusions of the anterior circulation, treated within 6 hours with mechanical thrombectomy by either ADAPT or the Solitaire stent. Th primary outcome was complete recanalization (modified TICI ≥ 2b); secondary outcomes included complication rates and procedural and clinical outcomes.RESULTS: From November 2012 to June 2014, 119 patients were treated with stent retriever (Solitaire FR) and 124 by using the ADAPT with Penumbra reperfusion catheters. The median baseline NIHSS score was the same for both groups (Solitaire, 17 [interquartile range, 11–21] versus ADAPT, 17 [interquartile range, 12–21]). Time from groin puncture to recanalization (Solitaire, 50 minutes [range, 25–80 minutes] versus ADAPT, 45 minutes [range, 27–70 minutes], P = .42) did not differ significantly. However, compared with the Solitaire group, patients treated with ADAPT achieved higher final recanalization rates (82.3% versus 68.9%; adjusted relative risk, 1.18; 95% CI, 1.02–1.37; P = .022), though differences in clinical outcomes between the cohorts were not significant. Use of an adjunctive device was more frequent in the ADAPT group (45.2% versus 13.5%, P < .0001). The rate of embolization in new territories or symptomatic hemorrhage did not differ significantly between the 2 groups.CONCLUSIONS: Front-line ADAPT achieved higher recanalization rates than the Solitaire device. Further randomized controlled trials are warranted to define the best strategy for mechanical thrombectomy.ADAPTA Direct Aspiration, First Pass Technique for the Endovascular Treatment of StrokeMTmechanical thrombectomymTICImodified TICI